Educação socialmente responsável : expressões no ensino de graduação em universidade comunitária - Silva, Inês Amaro da (2014)
The Socially Responsible University, in the context of university-society relations, has been associated with quality in the perspective of social pertinence, by means of managing teaching processes, research, extension and institutional management, which may contribute for facing issues concerning the legitimacy and sustainability of universities in the contemporaneity. In addition, the Socially Responsible Education, under the Socially Responsible University, regards academic processes on humanistic and professional training, fulfilling the Social Responsible mission of the university, and occurring, mainly, in ethics and citizenship training. Moreover, this study has approached the perspective of complex thinking by Edgar Morin, and, in the context of the ethics management of educational impacts by François Vallaeys, both emergent subjects of the higher education scenario in this century. Furthermore, this research has sought to understand the Socially Responsible Education, its expressions and potentialities in the context of the Community University, aiming to contribute for the elaboration and/or qualification of educational policies and strategies towards ethics and citizenship training, and the advance of Socially Responsible management in the university as well. Through a qualitative approach, this study has not only identified the manifestations of the Socially Responsible University in the institutional planning and strategies of PUCRS, but also analyzed the expressions of Socially Responsible Education in the graduate teaching at this university. Beyond that, this research has carried out a documental analysis of the set of Pedagogical Course Projects, approved from 2009 to 2013, based on items such as socio-environmental responsibility and graduate profile; it has also investigated the perceptions of students from different courses on Socially Responsible Education and possible impacts on their ethics and citizenship training, through a focus group. The results have revealed the potential and diversity of ongoing institutional initiatives under the Socially Responsible University, and, more accurately, the Socially Responsible Education as well as identifying opportunities for the integration of these initiatives in a sustainable management pattern. Even if the predominant conception of social responsibility comes from the social commitment through the realization of community actions, Socially Responsible Education, ethics and citizenship training have been expressed in different fundaments, principles, strategies and institutional initiatives, highlighting the curriculum subjects that have treated these topics and theory-practical experiences in the social reality. Therefore, the perception of students has been fostering these expressions and revealing conceptions, gaps and expectations in relation to the role of the university in the Socially Responsible training. Thus, the results of this research have pointed to challenges and dilemmas to be faced when consolidating and fortifying SER in the university, from which some strategies have been suggested to be implemented on the management, and that are going to serve as an inspiration to this and other realities in the higher education field. Complex thought and emergent rationalities, which foster new pedagogical theories, have been taken as the bases for the Socially Responsible Education in the contemporaneity and its potentiality, in order to mobilize and reflect socially responsible processes associated with quality, being socially pertinent in the Community University, and considered as boosters of the new future.